Iklim Organisasi dan Work Engagement Karyawan Generasi Millenial - A. Zhafirah Anisa Putri; Resekiani Mas Bakar; Rahmawati Syam (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
Millennials constitute one of the workforce groups that dominate human resources in various organizations. Their characteristics, including being goal-oriented, seeking work flexibility, and expecting a supportive work environment, make work engagement an important factor in enhancing their performance and contribution to organizations. However, despite their increasing dominance in the workplace, many organizations still face the challenge of low work engagement, which is reflected in declining enthusiasm, commitment, and employees' psychological attachment to their work. One factor that is presumed to influence the level of work engagement is organizational climate, which is reflected in employees' perceptions of the work environment, organizational support, interpersonal relationships, and the systems and policies implemented within the company. This study aims to examine the effect of organizational climate on work engagement among millennial employees in Makassar City. The study employed a quantitative approach using regression analysis. The respondents consisted of 350 millennial employees in Makassar City selected through accidental sampling. The results indicate that organizational climate has a positive and significant effect on work engagement (B = 0.288; p = 0.000 < 0.05). The higher the organizational climate perceived by employees, the higher their level of work engagement. These findings highlight the importance of organizational attention to organizational climate in order to enhance work engagement among millennial employees.